Brain Boron Level, DNA Content, and Myeloperoxidase Activity of Metformin-Treated Rats in Diabetes and Prostate Cancer Model - YARAT, AYŞEN (SPRINGERNATURE, 2022)
In this study, the effect of metformin on boron levels and oxidative brain damage in rats due to diabetes and prostate cancer was investigated for the first time. Myeloperoxidase (MPO) activity and the amount of DNA were investigated as tissue oxidative and toxic damage parameters. In Copenhagen rats, Dunning prostate cancer was induced using high metastatic MAT-Lylu cells and diabetes was induced by single dose of streptozotocin (STZ) injection. Metformin was administered for 14 days after diabetes and prostate cancer induced. The rats were divided into six groups as follows: control group, diabetic group (D), cancer group (C), diabetic + cancer (DC) group, cancer + metformin (CM) group, diabetic + cancer + metformin (DCM) group. At the end of the experiment, brains were removed. Significant decrease of brain boron levels and significant elevation of MPO activity and DNA levels were observed in D, C, and DC groups as compared to control group. The effect of diabetes induction on the brain boron levels was much more than prostate cancer induction. The administration of metformin with CM and DCM obviously declined MPO activity and increased brain boron levels almost near to control group level. In conclusion, this study shows that the protective effect of metformin against brain damage in STZ-induced diabetic rats with Dunning prostate cancer may also be related to increased boron levels. The boron levels may be a novel indicator of reduced toxic and oxidative stress. Furthermore, the distribution and mechanism of action of boron should be clarified.
Keywords: Diabetes; Dunning prostate cancer; Metformin; Boron; Myeloperoxidase; Brain damage; DIETARY BORON; METABOLISM; BEHAVIOR; DRUG